Effect of Carbon Source Variations on Growth, Physiological Stress, and Saponin Levels of Talinum paniculatum Gaertn. Adventitious Roots - Nindi Novia Erin; Arif Yachya; Alfinda Novi Kristanti; Djarot Sugiarso; Yosephine Sri Wulan Manuhara (Universitas Gadjah Mada, 2022)
Monosaccharide and disaccharide as carbon sources can affect the production of secondary metabolites. The study aims to determine the effect of variations in carbon sources on growth, physiological stress, and saponin levels of the adventitious roots of Talinum paniculatum Gaerthn. Adventitious roots are subculture in liquid MS medium treated with various sugars: 3% sucrose, 3% glucose, 3% fructose, 3% lactose, 3% maltose, 3% dextrose, sucrose + fructose (1.5% + 1.5%), sucrose + glucose (1.5% + 1.5%), glucose + fructose (1.5% + 1.5%), sucrose + dextrose (1.5% + 1.5%) for 6 weeks. The results of this study show that the 3% fructose treatment produces the highest fresh and dry biomass, which are 1.30 g and 0.23 g compared to the control. The morphology of adventitious roots in the treatment of carbon source variation is not different from the control treatment. The highest MDA (malondialdehyde) levels are found in the sucrose + fructose treatment (1.5% + 1.5%). Meanwhile, the highest proline levels are found in the 3% maltose treatment. Saponin levels analyzed using thin layer chromatography show the data in the form of color intensity and stain area based on ImageJ software analysis. The 3% fructose treatment shows the highest color intensity and stain area compared to the control. Variations in carbon sources affect physiological stress, biomass, and saponin levels of adventitious roots of T. paniculatum, but do not effect on root morphology.